MORPHOLOGICAL STUDY OF RAT’s BRAIN DUE TO EXPERIMENTAL PORPHYRINOPATHYA - Kryzhnaya, S.I.; Laryanovskaya, J.B. (World of Medicine and Biology, 2012)
There are shown the results of changed morphological parameters in the different brain regions (cerebral cortex, cerebellar cortex, midbrain) due to disturbed porphyrine metabolism. It is shown that under these conditions there are structural and functional changes of neurons in the different brain regions of rats. Neurotoxic effect is provided not only qualitative but also quantitative indices (index of alteration, glio-neuronal index, perineyronalny satellite index) damage. Degenerative changes of neurons, forming neyrono degenerative processes due to such conditions occur in the context of microcirculatory changes in all areas of the brain and are associated with perivascular edema and hypoxia, which leads to disruption of neuronal trophism. The morphological changes of the cerebral cortex are the most damaged zone and the cerebellar cortex - the least damaged area of the brain due to experimental porphyria.